The Prevalence of Obesity in Children with Asthma - حكيم, مأمون; محمد, علي; باش بيوك, ألفت (Latakia University Journal -Medical Sciences Series, 2020)
Objective: Asthma and Obesity are two of the most common chronic diseases in the world, and their prevalence has increased in recent decades. The aim of this study is to calculate the prevalence rate of obesity in asthmatic children, and to determine the association between Body mass index (BMI) and asthma severity. Methods: An observational descriptive cross-sectional study of 260 child, who presented to the emergency department Tishreen University Hospital in Lattakia between 2018-2019. BMI was determined in all children .Obesity was defined as BMI greater than 95% percentil. Asthma severity was defined by using National Asthma Education And Prevention (NAEPP). Results: The study sample included 260 asthmatic children (162 male-98 female). The prevalence of obesity in the total sample was 17.3% and at a higher rate among males by 64.4%.Using the correlation coefficient, the study showed a positive relationship between body mass index and severity of asthma, and also an inverse relationship between the body mass index and peak experatory flow rate, The study showed that obesity is a risk factor for persistent asthma compared to intermittent asthma. Conclusions: This study showed the important prevalence of obesity in asthmatic children, which calls for more awareness about this problem to limit the height rates by weight management and increasing physical activity to improve asthmatic symptoms and quality of life. This study supports the positive relationship between obesity and asthma, and it is indicates that obesity may be a potentially modifiable risk factor for asthma.